2018
DOI: 10.1016/j.jhydrol.2017.12.064
|View full text |Cite
|
Sign up to set email alerts
|

Development of a methodology to assess future trends in low flows at the watershed scale using solely climate data

Abstract: 1Low flow conditions are governed by short-to-medium term weather conditions or long term 2 climate conditions. This prompts the question: given climate scenarios, is it possible to 3 assess future extreme low flow conditions from climate data indices (CDIs)? Or should we 4 rely on the conventional approach of using outputs of climate models as inputs to a 5 hydrological model? Several CDIs were computed using 42 climate scenarios over the years 6 1961 to 2100 for two watersheds located in Québec, Canada. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 96 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…Since the early 1980s, the hydrological model HYDROTEL (Fortin et al, 1995(Fortin et al, , 2001Turcotte et al, 2007) has been developed by a group of researchers at the "Institut National de Recherche Scientifique" (INRS) in Quebec City, Canada. It has been applied on several watersheds-especially over the Quebec province-to study, among other things, the impacts of hydrological model structure in climate change impact assessment studies (Chen et al, 2011;Poulin et al, 2011;Velazquez et al, 2013), the simulation of the effects of wetlands on watershed hydrology under current and future climate and land cover conditions (e.g., Blanchette et al, 2019;Fossey et al, 2015Fossey et al, , 2016Fossey & Rousseau, 2016a, 2016b, the simulation of snow water equivalent (SWE; Oreiller et al, 2014), and the assessment of future trends in low flows (Foulon et al, 2018). Since many years, HYDROTEL is the main hydrological model used operationally at the Direction de l'Expertise Hydrique (Québec's Water Expertise Direction) for short-term flow forecasting (Turcotte et al, 2004) and for simulating the impacts of climate change on river flows as part of the Hydroclimatic Atlas of Southern Quebec (DEH, 2018a).…”
Section: Methodology and Experimental Setupmentioning
confidence: 99%
“…Since the early 1980s, the hydrological model HYDROTEL (Fortin et al, 1995(Fortin et al, , 2001Turcotte et al, 2007) has been developed by a group of researchers at the "Institut National de Recherche Scientifique" (INRS) in Quebec City, Canada. It has been applied on several watersheds-especially over the Quebec province-to study, among other things, the impacts of hydrological model structure in climate change impact assessment studies (Chen et al, 2011;Poulin et al, 2011;Velazquez et al, 2013), the simulation of the effects of wetlands on watershed hydrology under current and future climate and land cover conditions (e.g., Blanchette et al, 2019;Fossey et al, 2015Fossey et al, , 2016Fossey & Rousseau, 2016a, 2016b, the simulation of snow water equivalent (SWE; Oreiller et al, 2014), and the assessment of future trends in low flows (Foulon et al, 2018). Since many years, HYDROTEL is the main hydrological model used operationally at the Direction de l'Expertise Hydrique (Québec's Water Expertise Direction) for short-term flow forecasting (Turcotte et al, 2004) and for simulating the impacts of climate change on river flows as part of the Hydroclimatic Atlas of Southern Quebec (DEH, 2018a).…”
Section: Methodology and Experimental Setupmentioning
confidence: 99%
“…The trend of the annual minimum daily flow time series will be tested using the Mann-Kendall (M-K) method and the Pettitt change point analysis will be employed to determine the change point [49][50][51]. The M-K test is a rank-based nonparametric trend detection method that is commonly used to assess the significance of monotonic trends in hydrological data time series [40,[52][53][54]. The null hypothesis for no-trend in the M-K test is that the low flow time series are randomly ordered.…”
Section: Nonstationary and Trend Test Methodsmentioning
confidence: 99%
“…A growing number of studies have recently been focused on investigating low streamflow responses to climate change (Marx et al 2018, Mahmoodi et al 2020, Ghafouri-Azar et al 2021. Several studies were conducted to look into the future of low streamflow variations estimations under various climate change scenarios (Foulon et al 2018, Fangmann & Haberlandt 2019, Jehanzaib et al 2020. Another research examined the long-term historical trends of observed hydro-climatic factors and discovered probable connections between low streamflows and climatic variables to determine the influence of climate change on low streamflows (Degefu & Bewket 2017, Konapala et al 2018, Dudley et al 2020.…”
Section: Introductionmentioning
confidence: 99%